2013
DOI: 10.12688/f1000research.2-21.v2
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between miRNA-targeted-gene promoter methylation and miRNA regulation of target genes

Abstract: Science and Technology Norway Discuss this article AbstractmiRNA regulation of target genes and promoter methylation are Background known to be the primary mechanisms underlying the epigenetic regulation of gene expression. However, how these two processes cooperatively regulate gene expression has not been extensively studied.Gene expression and promoter methylation profiles of 271 distinct Methods human cell lines were obtained from gene expression omnibus. P-values that describe both miRNA-targeted-gene pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…We also report that the level of promoter methylation and N miR have the greatest influence on protein evolutionary rates, and they have a dependent effect on the rate of mammalian protein evolution. This result supports the previously hypothesized potential reciprocal regulation between these two regulatory factors ( Taguchi 2013a , 2013b ).…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also report that the level of promoter methylation and N miR have the greatest influence on protein evolutionary rates, and they have a dependent effect on the rate of mammalian protein evolution. This result supports the previously hypothesized potential reciprocal regulation between these two regulatory factors ( Taguchi 2013a , 2013b ).…”
Section: Introductionsupporting
confidence: 92%
“…Recent studies reported that promoter methylation and miRNA may coregulate their target genes. Changes in promoter methylation may affect miRNA targeting, suggesting a mutual correlation between miRNA-mediated regulation of target genes and miRNA-targeting-specific promoter methylation in brain ( Taguchi 2013a , 2013b ). Promoter methylation of miRNA-targeted genes has also been suggested to be highly correlated with miRNA seed region features ( Taguchi 2013b ).…”
Section: Resultsmentioning
confidence: 99%
“…10,11 Although MiRaGE was originally invented to infer miRNA regulation of target gene expression from target mRNA expression, it has also been used successfully to infer miRNA regulation of promoter methylation. 2,3 Briefly, MiRaGE first computes the amount of differential mRNA expression/promoter methylation/histone modification of the ith gene at the jth sample, ∆x ij (see below for actual definition). It then computes the differential values to group the genes into two sets: genes targeted by the considered miRNA, or genes not targeted by the considered miRNA but targeted by any other miRNAs.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Su et al 1 found that miRNAs more frequently target genes with less methylated promoters. More recently, the author used bioinformatics to identify apparent reciprocal regulation of target genes between promoter methylation and miRNAs, 2,3 which has some support from the evolutionary point of view. 4 Thus, seeking more examples of apparent miRNA regulation of other epigenetic factors will deepen our understanding of the epigenetic regulation of mRNAs.…”
Section: Introductionmentioning
confidence: 99%